Approaches to Methodology Used For the Prospects and Difficulties Of Treating a Sin-gle Account in a Developing Country: Nigeria's Economic Growth and Development. - Ajiteru, S.A.R; Sulaiman, T.H; Abalaka, J.N (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the potential and challenges of the Treasury Single Account (TSA), which the cur-rent government of Nigeria has recently fully implemented to drive economic growth and development. The government aims to close gaps and plug leaks in government funds while ensuring a robust finan-cial management system to guarantee transparency and efficiency in the administration of public fi-nancial resources. The paper provides a conceptual understanding of TSA and discusses its anticipated benefits to Nigeria’s economy, particularly in the context of financial management and control. Key benefits include reducing the cost of government borrowing, ensuring optimal utilization of govern-ment financial resources, and consolidating various government accounts into one unified account. The study also examines the structure of the TSA system and its various accounts, including the TSA pri-mary account. In addition, the paper highlights the goals of the TSA, such as improving accountability and reducing corruption. After discussing the potential and challenges associated with implementing the TSA, the study concludes that political will, integrity, and commitment are crucial for overcoming these challenges. Successful implementation of the TSA system requires addressing identified obstacles to realize the anticipated benefits, which would significantly enhance the efficiency of financial man-agement in Nigeria.